The Role of Teachers in Instilling Digital Citizenship Education - Matang, Matang; Lisman, Muhammad; Simah Bengi, Elsi (Jurnal Edukasi Terkini, 2025)
Purpose-The development of digital technology presents challenges in shaping the character of citizens, especially for the younger generation growing up in a digital environment. Digital Citizenship Education is a strategic effort to prepare students to use technology responsibly, critically, and ethically. Research Methodology/Design/Approach-This study aims to analyze the role of teachers in instilling digital citizenship values ​​in educational settings. Result-Through literature analysis, it was found that teachers play a role as facilitators, role models, and curriculum developers capable of integrating digital literacy values, social media ethics, and legal awareness in the digital world into the learning process. Therefore, teachers are required to improve their digital competencies to provide guidance relevant to the needs of the times. Originality / Value-The success of digital citizenship education in schools depends heavily on teachers' readiness and commitment to internalizing citizenship values ​​appropriate to the context of the digital era.